Enzymatic debridement for the treatment of severely burned upper extremities – early single center experiences. Issue 1 (December 2016) - Cordts, Tomke; Horter, Johannes; Vogelpohl, Julian; Kremer, Thomas; Kneser, Ulrich; Hernekamp, Jochen-Frederick
Abstract Background Severe burns of hands and arms are complex and challenging injuries. The Standard of care (SOC) – necrosectomy with skin grafting – is often associated with poor functional or aesthetic outcome. Enzymatic debridement (ED) is considered one promising alternative but, until recently, results proved to be highly variable. Methods Between 04/2014 and 04/2015, 16 patients with deep partial- to full-thickness burns of the upper extremities underwent enzymatic debridement (ED) in our Burn Center and were evaluated for extent of additional surgery, wound healing, pain management and functional parameters. Results Following ED, no further surgical intervention was required in 53.8 % of the study population. In patients who required surgical treatment, the the skin-grafted area could be reduced by 37.0 % when compared to initial assessment. Time from injury to ED was 24.4 h and patients were able to start physical therapy after 2.0 days but suffered from prolonged wound closure (28.0 days). Regionally administered anesthesia proved to be superior to pain medication alone as pain levels and consumed morphine-equivalent were lower. Post-demission follow-up showed good functional results and pain levels with low scores in two self-report questionnaires (DASH, PRWE-G) but 3 patients reported increased susceptibility to shear stress. Based on these early experiences, we developed a 3-step algorithm for consecutive patients allowing appropriate and individualized treatment selection. Conclusions We see a potential benefit for ED in the treatment of severely burned hands and forearms but further investigations and proper prospective, randomized controlled trials are needed to statistically support any outlined assumptions.